An Analysis of Structural Units and Modification of the Idiomatic Expressions on Speech Videos - Putri, Devara Arisa; Mutiara, Rika (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research analyzed idiomatic expressions in speech videos on the TEDx Talks YouTube channel. This study used descriptive linguistics to collect qualitative data and used analytical techniques. The data were taken from nine speech videos from TEDx Talks YouTube channel, after collected the idiomatic expressions, the data were categorized using two theories: Biber’s (1999) and Ernst’s (1981) theories. This study found 54 kinds of structural units of idiomatic expressions with the most dominant were prepositional phrase idioms with total 21 idioms, followed by selected verb + noun phrase idioms with total 14 idioms, next selected verb + prepositional phrase idioms with total 13 idioms, and lastly noun phrase idioms with total 6 idioms. This study also found 11 idiom modifications, and internal modifications were the most appeared with total 5 idioms, followed by external modifications with total 4 idioms, and lastly conjunction modification with total 2 idioms. The implications of this research can be used in teaching and learning for EFL/ESL.